Brief considerations on easements in the Civil Code of 2002 (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The present article makes a brief study on the legal regime of predial servitudes in the Civil Code of 2002. It is a research that uses descriptive methodology, based fundamentally on bibliographical research. The most relevant issues are analyzed, such as the definition of servitudes, their legal nature, classification, characteristics, use and extinction. The study makes clear to the reader that the Civil Code of 2002 reinforced the idea of cooperation in servitude, particularly with regard to the provisions on compulsory expansion and removal of servitude. Thus, the attribution of the usefulness of one property in favor of another, seeking the best use of both, attends to sociological reasons, whose origins are found in the Federal Constitution, which defines the requirement of attending to the social function of the property.
Keywords: predial servitudes; personal servitudes; property; social function of property; private law